Tooth-Loss Experience and Associated Variables among Adult Mexicans 60 Years and Older - Islas-Granillo, Horacio; Borges-Yañez, Aida; Medina-Solis, Carlo Eduardo; Lucas-Rincón, Salvador Eduardo; Navarrete-Hernández, José de Jesús; Villalobos-Rodelo, Juan José; Casanova-Rosado, Juan Fernando; Maupomé, Gerardo (Puerto Rico Health Sciences Journal, 2016)
Objective: This study was conducted to determine the experience of tooth loss, as well as its associated variables, in a sample of adult Mexicans, aged 60 years and older. Materials and Methods: This cross-sectional study was part of a larger project to measure diverse oral health indicators in a convenience sample: it included 139 adult Mexican seniors (69.1% of whom were women), ages 60 years and older, either living in long-term care facilities or living independently and participating in adult day care services. Each participant underwent an oral examination to determine the number of missing teeth. Questionnaires were administered to collect sociodemographic, socioeconomic, and behavioral data. Statistical analyses were performed using nonparametric tests and negative binomial regression. Results: The mean age was 79.06 (±9.78 years). The mean number of missing teeth was 20.02 (±8.61; median, 24); 99.3% of the participants had at least 1 missing tooth, and only 14 had 20 teeth or more. Using a negative binomial regression multivariate model, we found that for each year’s increase in age, the mean number of teeth lost increased by 1% (p<0.05). In individuals who brushed their teeth fewer than two times a day, who had received radiotherapy, or who were currently smokers, the average tooth loss increased 49.2%, 22.6%, and 19.0%, respectively (p<0.01). Conclusion: Tooth-loss experience in these Mexican seniors was very high (20.02±8.61). Older age (within the range of this group of seniors), tooth-brushing patterns, the receipt of radiation therapy, and (current) tobacco use were associated with higher experience of tooth loss.